Frailty in Older Patients Undergoing Emergency Laparotomy: Results From the UK Observational Emergency Laparotomy and Frailty (ELF) Study. Issue 4 (April 2021) - Parmar, Kat L.; Law, Jennifer; Carter, Ben; Hewitt, Jonathan; Boyle, Jemma M.; Casey, Patrick; Maitra, Ishaan; Farrell, Ian S.; Pearce, Lyndsay; Moug, Susan J.
Abstract : Objective: This study aimed to document the prevalence of frailty in older adults undergoing emergency laparotomy and to explore relationships between frailty and postoperative morbidity and mortality. Summary Background Data: The majority of adults undergoing emergency laparotomy are older adults (≥65 y) that carry the highest mortality. Improved understanding is urgently needed to allow development of targeted interventions. Methods: An observational multicenter (n=49) UK study was performed (March–June 2017). All older adults undergoing emergency laparotomy were included. Preoperative frailty score was calculated using the progressive Clinical Frailty Score (CFS): 1 (very fit) to 7 (severely frail). Primary outcome measures were the prevalence of frailty (CFS 5–7) and its association to mortality at 90 days postoperative. Secondary outcomes included 30-day mortality and morbidity, length of critical care, and overall hospital stay. Results: A total of 937 older adults underwent emergency laparotomy: frailty was present in 20%. Ninety-day mortality was 19.5%. After age and sex adjustment, the risk of 90-day mortality was directly associated with frailty: CFS 5 adjusted odds ratio (aOR) 3.18 [95% confidence interval (CI), 1.24–8.14] and CFS 6/7 aOR 6·10 (95% CI, 2.26–16.45) compared with CFS 1. Similar associations were found for 30-day mortality. Increasing frailty was also associated with increased risk of complications, length of Intensive Care Unit, and overall hospital stay. Conclusions: A fifth of older adults undergoing emergency laparotomy are frail. The presence of frailty is associated with greater risks of postoperative mortality and morbidity and is independent of age. Frailty scoring should be integrated into acute surgical assessment practice to aid decision-making and development of novel postoperative strategies. Abstract : Supplemental Digital Content is available in the text